Pendampingan Implementasi Sistem Informasi Klinik untuk Optimalisasi Pelayanan di BPM Dhiaulhaq - Nurwidiana, Nurwidiana; Fatmawati, Wiwiek (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2025)
Clinical information systems play a strategic role in enhancing service quality, expediting administrative processes, improving dataaccuracy, and minimising the risk of errors. This community service program aimed to implement a clinical information system at the Independent Midwifery Practice (BPM) Dhiaulhaq. The method employed was participatory community empowerment using the Participatory Rural Appraisal (PRA) approach, which emphasises active involvement of the partner throughout all stages of the activity. The implementation process included system development tailored to the partner’s needs, software installation, user training,and operational assistance. The results demonstrated successful digitalization of medical records, significantly improving serviceefficiency, particularly in patient registration and medication management. The partner is interested in future system development to support financial management functions.